2018
DOI: 10.1002/jcla.22669
|View full text |Cite
|
Sign up to set email alerts
|

Association of VDR‐FokI and VDBP‐Thr420Lys polymorphisms with cervical spondylotic myelopathy: A case‐control study in the population of China

Abstract: Background: Cervical spondylotic myelopathy (CSM), a common degenerative disorder, is characterized by chronic progressive compression of the cervical spinal cord.The present case-control study aimed to explore the potential role of VDR-FokI and VDBP-Thr420Lys polymorphisms in the susceptibility to CSM in the Chinese population. Methods: The study enrolled 318 CSM patients and 282 healthy individuals whose clinical data were retrospectively analyzed. Polymerase chain reaction-restriction fragment length polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The BsmI polymorphism also had no effect on CSM risk, but the ApaI and TaqI polymorphisms conferred a 2.88 times and 4.67 times increased CSM risk (both p < 0.001). In opposition to Wang et al's findings, Song et al (2018) found the ff genotype of the FokI polymorphism to be associated with a 1.985 times greater risk of myelopathy (p = 0.003) [49].…”
Section: Spinal Cord Pathologymentioning
confidence: 63%
See 2 more Smart Citations
“…The BsmI polymorphism also had no effect on CSM risk, but the ApaI and TaqI polymorphisms conferred a 2.88 times and 4.67 times increased CSM risk (both p < 0.001). In opposition to Wang et al's findings, Song et al (2018) found the ff genotype of the FokI polymorphism to be associated with a 1.985 times greater risk of myelopathy (p = 0.003) [49].…”
Section: Spinal Cord Pathologymentioning
confidence: 63%
“…There was no effect of the Thr420Lys polymorphism of the VDBP gene on mJOA score or the number of ossified segments in 318 CSM patients [49]. Similarly, four polymorphisms of the VDR gene (FokI, BsmI, ApaI, TaqI) were found to have no significant effect on mJOA score in two studies [49,51].…”
Section: What Are the Genetic Effects On Clinical Severity Of Dcm?mentioning
confidence: 90%
See 1 more Smart Citation
“…We set a standard 40,43 genome-wide significance threshold of 5×10 −8 . We also specifically examined 63 genetic markers identified as significantly associated with DCM in prior literature 6,11,44–77 . For these markers, a Bonferroni-adjusted P -value of <0.0008 (=0.05/63) and an OR indicating an association in the same direction as the original publication were considered evidence of replication.…”
Section: Methodsmentioning
confidence: 99%